2016
DOI: 10.1177/1357633x16638971
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on cost-effectiveness of home-based motor assessment in Parkinson’s disease

Abstract: Introduction Treatment adjustments in Parkinson's disease (PD) are in part dependent on motor assessments. The aim of this study was to evaluate the cost-effectiveness of home-based motor monitoring plus standard in-office visits versus in-office visits alone in patients with advanced PD. Methods The procedures consisted of a prospective, one-year follow-up, randomized, case-control study. A total of 40 patients with advanced PD were randomized into two groups: 20 patients underwent home-based motor monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 33 publications
1
66
0
Order By: Relevance
“…It is convenient for health care centers to establish routines for video consultation (see the section on Telemedicine). Apart from the consultation, it can also be valuable to get objective and quantitative monitoring of a patient's status, 32,33 for example, monitoring the status of the PEG (Fig. 3A).…”
Section: Care Of Lcig Patients In Times Of Humanitarian Crisismentioning
confidence: 99%
“…It is convenient for health care centers to establish routines for video consultation (see the section on Telemedicine). Apart from the consultation, it can also be valuable to get objective and quantitative monitoring of a patient's status, 32,33 for example, monitoring the status of the PEG (Fig. 3A).…”
Section: Care Of Lcig Patients In Times Of Humanitarian Crisismentioning
confidence: 99%
“…For people with PD, being tested at home could enable better appreciation of some activities of daily living (ADLs) which occur more naturally away from a clinic or lab environment [20], rare events such as falls [21], activities which impact upon wellbeing and quality of life [22] and outcomes such as sleep quality which are costly and logistically difficult to measure longitudinally in the clinic/lab. Technology deployed to the home could provide measurements to the clinician/researcher which would otherwise have required clinician time to obtain [23], have scalability to large numbers of people with PD remotely [24], and reduce the cost of clinic visit/clinical trial contacts [25]. An extrapolation is that the home setting could improve generalisability in outcome measure results, for example by increasing inclusivity towards those people living outside the radius of a clinical treatment unit.…”
Section: Testing In the Home Or Home-like Settingmentioning
confidence: 99%
“…The studies were set in the participants' real home setting with only infrequent exceptions [37][38][39][40]. Home-based testing may be beneficial in PD partly to cater for those patients who are limited geographically or practically from attending frequent clinic assessments [103], partly to save costs [25] and importantly to achieve ecological validity in the assessment of PD symptoms which are poorly captured in 'snap-shot' reviews in a laboratory or clinic environment [8].…”
Section: Types Of Studiesmentioning
confidence: 99%
“…Studies have shown high acceptance and usage compliance of wearable sensors by individuals with PD [2628]. A recent study demonstrated that home-based motor monitoring can provide cost-effective clinical information and help enhance care for patients with advanced PD [6]. Likewise, studies have shown live videoconferencing may be able to provide similar clinical benefit to in-person care for patients with PD [3, 2931].…”
Section: Introductionmentioning
confidence: 99%